Diagnostic Importance of MRI and CT Scans for Synovial Osteochondromatosis of the Temporomandibular Joint - VAROL, ALTAN; DUMLU, ASIM (TAYLOR & FRANCIS LTD, 2011)
Since synovial chondromatosis (SC) clinically mimics symptoms of internal derangements of the TMJ, the diagnostic value of MRI and CT, overlooked for years, is discussed in the presented case. Multiple amorphous calcifications in the left infratemporal fossa and upper synovial compartment of the TMJ were detected on the CT and MRI scans. The patient underwent open TMJ arthrotomy and removal of 15 calcified loose bodies. SC may be diagnosed radiographically when sclerosis of the glenoid fossa, soft tissue edema, and intraarticular radio-opaque loose bodies are detected. Advanced imaging of the TMJ, such as MRIs and CTs, are indispensible methods to obtain differential diagnoses for long-standing suspicious pathologies of the temporomandibular joint.
Keywords: CHONDROMATOSIS